Relationship between prenatal care and maternal complications in women with preeclampsia: Implications for continuity and discontinuity of prenatal care - Ching-Ming Liu; Shuenn-Dyh Chang; Po-Jen Cheng (Taiwanese Journal of Obstetrics & Gynecology, 2012)
Objective: Prenatal care is associated with better pregnancy outcome and may be a patient safety issue. However, no studies have investigated the types and quality of prenatal care provided in northern Taiwan. This retrospective study assessed whether the hospital-based continuous prenatal care model at tertiary hospitals reduced the risk of perinatal morbidity and maternal complications in pre-eclampsia patients. Materials and Methods: Of 385 pre-eclampsia patients recruited from among 23,665 deliveries, 198 were classified as patients with little or no prenatal care who received traditional, individualized, and physician-based discontinuous prenatal care (community-based model), and 187 were classified as control patients who received tertiary hospital-based continuous prenatal care. Results: The effects on perinatal outcome were significantly different between the two groups. The cases in the hospital-based care group were less likely to be associated with preterm delivery, low birth weight, very low birth weight, and intrauterine growth restriction. After adjustment of confounding factors, the factors associated with pregnant women who received little or no prenatal care by individualized physician groups were diastolic blood pressure ≥105 mmHg, serum aspartate transaminase level ≥150 IU/L, and low-birth-weight deliveries. This study also demonstrated the dose–response effect of inadequate, intermediate, adequate, and intensive prenatal care status on fetal birth weight and gestational periods (weeks to delivery). Conclusion: The types of prenatal care may be associated with different pregnancy outcomes and neonatal morbidity. Factors associated with inadequate prenatal care may be predictors of pregnancy outcome in pregnant women with pre-eclampsia.